Effectiveness of additional income for ASN at BKPSDMD Makassar City - Rakhman, Basri; Wijaya, Indra; Wahyuni, Ian; Rakhman, Muh Ikhsan (Linguistics and Culture Review, 2021)
Essentially, awarding the Employee with Additional employee Income (TPP) is expected to improve the welfare and performance of ASN to support development in Makassar and to provide better public services in Makassar. Therefore, this study aims to find out the Effectiveness of Providing Additional Employee Income (TPP), especially for ASN at BKPSDMD Makassar City, whether it has been effective in improving ASN performance or not. The research method used in this research is descriptive qualitative and descriptive quantitative data to optimize the result of the research findings. Interviews, observation, questionnaires, and document reviews are used to collect the data. The data analysis technique collects the data from the results of interviews, observations, questionnaires, and document reviews which are then presented systematically in descriptive form. The result shows that providing additional employee income (TPP) for ASN at BKPSDMD Makassar City has been effective, especially in improving the welfare of ASN. On the contrary, it is ineffective in terms of employee discipline. This is because the Leaders at BKPSDMD Makassar City do not set an excellent example regarding discipline. Moreover, Leaders are expected to set a good example of discipline and supervise the ASN.